Virtual goniometer using 3 space mocap sensors for lower limbs evaluation - Buele, Jorge (2020)
The deterioration of motor skills in lower limbs represents a reduction in people’s quality of life. This paper presents a virtual goniometer developed by the 3 Space Mocap sensors and Unity 3D software. The system shows lower limbs angles in real-time. This system helps physiatrists determine the movements of hip and knee and was compared with a goniometer to corroborate the system performance. To validate this prototype, comparative tests are carried out present a standard deviation of 1.86° and 2.12° in the left hip and knee respectively. Therefore, it confirms to be a reliable proposal for physical evaluations of lower limbs. © Springer Nature Switzerland AG 2020.